Uniaxial failure mechanism and design strength of high-strength welded hollow spherical joint. (1st April 2022) - Xing, Jihui; Qiu, Chen; Wang, Meiqi; Yang, Na
Highlights: The failure mechanism of high-strength welded hollow spherical joints is clarified. The basic mechanical properties of Q460 steel are obtained through tests. SWDM fracture model is developed to investigate the bearing capacity of the WHSJ. Four WHSJ full-scale specimens made of Q460 high-strength steel are tested. New design formulae for the bearing capacity of high-strength WHSJ are proposed. Abstract: High-strength large-span reticular shells have proliferated in recent years in engineering projects. Thus, appropriate rules should be developed to ensure the safe and efficient design of high-strength welded hollow spherical joints (WHSJ). However, to date, even the compressive failure mechanism of normal-strength WHSJ has not been fully recognized yet. In this paper, the failure mechanism and load bearing capacity of high-strength WHSJ are experimentally studied with four Q460 steel full-scale specimens under uniaxial loads. Also, three-dimensional refined finite element (FE) models are built, and their numerical results are shown to be in good agreement with experimental data. In addition, a micromechanical ductile fracture model, which can account for the effects of both stress triaxiality and Lode angle, is incorporated in FE models to improve the accuracy of joint failure prediction. Furthermore, focusing on the rib stiffener, the effects of two parameters, including the diameter-to-thickness ratio of the spherical joint and the ratio of spherical joint and chord diameters, on the performance of high-strength WHSJ are comprehensively studied. It was found that the failure of WHSJs subjected to uniaxial tension load is the punching shear rupture due to fully developed plastic strain, while the collapse of the WHSJs subjected to uniaxial compression load is caused by elasto-plastic buckling. Finally, new design formulae for the bearing capacity of high-strength WHSJ are proposed and validated using parametric analysis. It will be shown that these formulae help eliminate the potential risk in current specification provisions.